Pandemic or Generational War? - Solarz, Jan Krzysztof; Waliszewski, Krzysztof (Journal of Finance and Financial Law, 2020)
The article deals with the COVID-19 coronavirus pandemic and its potential impact on the economy, public finance system and personal finances. The shock of the virus outbreak and expansion on a global scale poses enormous challenges to economies, public finances and health systems related to the threat of recession, drastic reduction in personal income in households, the need to develop government programs mitigating the effects of a pandemic, and the central bank joining in the form of rate cuts interest and reserve requirements, as well as the launch of non-standard monetary policy instruments quantitative easing (QE). The aim of the study is to propose a language of nanofinance to describe a pandemic as a destruction of the mechanism of intergenerational and intra-generational solidarity. The main hypothesis of the study is that the quality of financial risk management of everyday life will determine the scale of financial losses and the time necessary to overcome the socio-economic collapse caused by a pandemic.